2014
DOI: 10.1371/journal.pone.0101994
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Drosophila HSP70 Promoter with Different HSE Numbers in Human Cells

Abstract: The activation of genetic constructs including the Drosophila hsp70 promoter with four and eight HSE sequences in the regulatory region has been described in human cells. The promoter was shown to be induced at lower temperatures compared to the human hsp70 promoter. The promoter activity increased after a 60-min heat shock already at 38°C in human cells. The promoter activation was observed 24 h after heat shock for the constructs with eight HSEs, while those with four HSEs required 48 h. After transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In general, this mechanism is thought to be primitive and conserved in eukaryotes, and to involve activation of HSP70 by interaction between HSF and HSE. Although the copy number of the HSE element was positively correlated with the induced strength of the hsp70 promoter (Kust et al 2014, Ortner et al 2015, no studies have reported interactions between HSE and other cisacting elements. In Uphsp70, we demonstrated that neither HSE nor LTR could solely retain the high promoter activity regardless of under heat or cold temperature.…”
Section: Synergistic Effects Of Hse and Ltr In Uphsp70mentioning
confidence: 99%
See 4 more Smart Citations
“…In general, this mechanism is thought to be primitive and conserved in eukaryotes, and to involve activation of HSP70 by interaction between HSF and HSE. Although the copy number of the HSE element was positively correlated with the induced strength of the hsp70 promoter (Kust et al 2014, Ortner et al 2015, no studies have reported interactions between HSE and other cisacting elements. In Uphsp70, we demonstrated that neither HSE nor LTR could solely retain the high promoter activity regardless of under heat or cold temperature.…”
Section: Synergistic Effects Of Hse and Ltr In Uphsp70mentioning
confidence: 99%
“…The HSE element was detected extensively from all species except for red seaweed Pyropia perforata. Additionally, the number of HSEs in a single sequence, which significantly positively correlates with induced strength of the hsp70 promoter activity (Kust et al 2014, Ortner et al 2015, varied from zero to five with species. Within algal or plant taxa, only slight variations were detected in the core sequences of HSE element containing 10 nucleotides ( Fig.…”
Section: Synergistic Effects Of Hse and Ltr In Uphsp70mentioning
confidence: 99%
See 3 more Smart Citations